Potential Causes and Consequences of Overlap in Talk between Speakers with Parkinson’s Disease and Their Familiar Conversation Partners - Griffiths, Sarah; Barnes, Rebecca; Britten, Nicky; Wilkinson, Ray (Seminars in Speech and Language, 2012)
Parkinson’s disease (PD) can cause both motor speech and cognitive deficits, with those affected perceiving a negative effect on their everyday experiences of communication. One specific concern reported by people with PD is that people “talk over” them. Psychosocial reactions to communication changes in PD are highly individualized and do not correlate strongly with measures of disease severity. With the aim of developing a better understanding of the individual’s everyday experience of being talked over, this study uses Conversation Analysis to examine videoed instances of naturally occurring overlapping talk. Two phenomena emerge. First, aspects of speech specific to PD can cause overlap, which in turn leads to the need for repair. Second, opportunities to repair disordered talk, further compromised in terms of intelligibility by overlap, are often not followed up. This leads to the deletion of PD turns at talk and therefore reduced participation in conversations. The implications of these phenomena for both client well-being and clinical interventions are discussed.
Keywords: parkinson’s disease; dysarthria; conversation analysis; overlap; repair